What mitzi wants: the koala brothers (Ladybird London, 2004)
Mitzi sees a beautiful toy in the shop window, but she doesn't have enough money to buy it. Luckily, with the help of Frank and Buster Mitzi runs lots of errands until she is able to save up and treat herself.